Rancang Bangun Mesin Pemotong Adonan Amplang Menggunakan Metode Nordic Body Map (NBM) dan Rapid Upper Limb Assessment (RULA) di PT Dzakira Citra Mandiri - Uslianti, Silvia; Putri, Titania; Wahyudi, Tri; Budiman, Riadi; Rahmahwati, Ratih (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The amplang dough cutting process at PT Dzakira Citra Mandiri was initially carried out manually using a non-ergonomic working posture, such as a bent body position and repetitive hand movements. These conditions potentially cause musculoskeletal complaints and increase ergonomic risks for operators. The initial evaluation using the Nordic Body Map (NBM) method showed a total complaint score of 145, which falls into the high-risk category, while the Rapid Upper Limb Assessment (RULA) resulted in a score of 6, indicating the need for immediate improvement. This study aims to design an ergonomically based amplang dough cutting machine by applying the NBM and RULA methods, as well as workers’ anthropometric data, to determine appropriate machine dimensions. The design process was conducted using CATIA software to produce a machine configuration that matches workers’ physical characteristics. After implementation, a re-evaluation showed a reduction in the NBM score to 77, classified as low risk, and a decrease in the RULA score to 4. In addition, the use of the machine improved work efficiency and ensured consistent amplang cutting sizes in accordance with production standards.